- Evaluation of serum Brain-derived Neurotrophic Factor, IL-6, IL-10, and TNF-α Cognitive Function, and Sleep Quality in Elderly Patients with Major Depressive Disorder and Somatic Symptoms: serum Brain-derived Neurotrophic Factor, IL-6, IL-10, and TNF-α Cognitive Function - Gao, Ya (Journal of Medical Biochemistry, 2025)
Objective: it aimed to analyze the relationship between somatization in elderly patients with major depressive disorder (MDD) and brain-derived neurotrophic factor (BDNF), IL-6, IL-10, and TNF-α cognitive function, and sleep quality(SQ). Method: 80 elderly patients with MDD were grouped based on the somatic self-rating scale (SSS): the subjects with somatic symptoms (SS) as the AG and the subjects without SS as the BG. Additionally, 25 healthy volunteers from the same period were included as the control group (CG). SQ scores, BDNF and its precursor (ProBDNF), and cognitive function scores of the subjects were collected. Result: the SQ and SS scores of AG and BG were visibly higher as against CG, and those of AG were visibly higher in contrast to BG; The cognitive function scores of AG and BG were visibly lower as against CG, and the score of AG was visibly lower in contrast to BG (P 0.05). CRP, IL-6, IL-10, and TNF-α in both AG and BG were visibly higher as against CG; Those were visibly higher in AG as against BG (P
Keywords: MDD in the elderly; serum Brain-derived Neurotrophic Factor, IL-6, IL-10, and TNF-α Cognitive Function, somatization symptoms